2021
DOI: 10.1590/198055272521
|View full text |Cite
|
Sign up to set email alerts
|

Mercado De Trabalho, Salário-Mínimo E Distribuição De Renda No Brasil No Passado Recente

Abstract: RESUMO O presente estudo trata da evolução do mercado de trabalho brasileiro e da distribuição de rendimentos do trabalho na recente desaceleração e crise da economia brasileira. Entre 2012 e 2019, ocorreram transformações significativas marcadas pelo aumento do desemprego e da informalidade, sobretudo em 2015 e 2016. Os indicadores de desigualdade de rendimentos, contudo, apresentaram tendência distinta, com continuidade da desconcentração que vinha sendo observada até 2016. A partir da utilização de duas fon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
0
0
0
2
Order By: Relevance
“…Por outro lado, o Plano Real iniciou uma política de estabilização monetária em 1994, com efeitos positivos sobre os índices de pobreza, e a desigualdade de renda do trabalho começou a diminuir em 1995 (Hoffmann, 2006;Rocha, 1996). Já em 1996, o salário-mínimo passou a ser valorizado acima da inflação (Sabóia, 2005).…”
Section: Criação E Evolução Do Seguro-desemprego No Brasilunclassified
“…Por outro lado, o Plano Real iniciou uma política de estabilização monetária em 1994, com efeitos positivos sobre os índices de pobreza, e a desigualdade de renda do trabalho começou a diminuir em 1995 (Hoffmann, 2006;Rocha, 1996). Já em 1996, o salário-mínimo passou a ser valorizado acima da inflação (Sabóia, 2005).…”
Section: Criação E Evolução Do Seguro-desemprego No Brasilunclassified
“…In this field we have Monsueto, Carrijo and Autor (2017) When it comes to the studies about Brazilian income inequality, those are dated especially to the time that Brazil faced a drop in inequality. The determinants for this downfall, according to some authors, were the program of income transference realized by the government called Bolsa Família, the real wage gains and the positive evolution of the labor market (SABOIA, 2007;BIANCARELLI, 2014;HOFFMANN, 2014;SANTOS, 2015). Some As long as we are facing several changes, mainly in the labor market and social security fields, the need for studies that brings this subject to the top again becomes fundamental.…”
Section: Labor Market Quality and Income Inequality In Brazilmentioning
confidence: 99%
“…(Herrero-Olarte & Sosa, 2020) found a correlation in Latin American countries, but with a small impact on the relationship between the increase in the MW and the increase in the lowest wages. (Saboia, Hallak, Simões, & Dick, 2021), for the case of Brazil, estimated a significant effect of the MW on low and middle levels of labour income, with the largest effect between the third and seventh decile, thus improving the countryʹs income distribution. However, other studies found no effect of the MW on earnings in the first two deciles of the distribution, an effect attributed to labour informality concentrated at the bottom of the wage distribution.…”
Section: Systematic Review From 2020 To 2024mentioning
confidence: 99%